Teacher Trainees' Epistemological Beliefs: Effects of Gender, Institution, and Discipline (Mathematics/Social Sciences) - (:unkn) unknown (WYDAWNICTWO ADAM MARSZALEK, 2009)
How knowledge is acquired in various disciplines or the existence of other knowledge sources have been the focus of more recent research. Three types of knowledge have been specified in relation to the teaching of a discipline content, pedagogical and pedagogical content knowledge. Teachers and teacher trainees are expected to have expertise on these three knowledge areas. Within the process individuals develop epistemological beliefs. Little research exists which studies how similar/different mathematics and social sciences students are in terms of their epistemological beliefs. Therefore, the aim of this research was to investigate whether mathematics and social sciences teacher trainees differed in terms of their epistemological beliefs and if they did to test these differences with regards to certain variables. The sample consisted of mathematics and social sciences teacher trainees registered at four departments of two education faculties at two universities in Turkey. The data was collected using an 'Epistemological Beliefs Scale and a background information schedule. The results indicated gender differences in all three sub-scales of the epistemological beliefs scale. A difference in terms of discipline was also observed in the 'belief that learning depends on ability' factor of the epistemological beliefs scale.
Keywords: epistemological beliefs; teacher trainees; STUDENTS; COMPREHENSION; KNOWLEDGE; COLLEGE